Consumer Choice of Retail Formats in Russian Grocery Sector - ДоморацкаяЮлия Вадимовна (Journal of Economic Sociology, 2012)
Analyzing the Russian Longitudinal Monitoring Survey data of 2006–2009 years, the author reveals three groups of consumers which differ in their shopping practices: those who buy food (1) only in traditional stores, (2) only in modern stores, (3) in modern and traditional stores. The article reveals social and economic factors providing an impact on consumers’ choice of retail formats.